Czas wolny dzieci i młodzieży mieszkającej na terenach miejskich - Matysiak-Błaszczyk, Agata (Studia Edukacyjne, 2023)
Free time of children and adolescents is an important and interesting issue addressed by scholars of many disciplines. The article presents the theoretical basis of knowledge on contemporary free time paradoxes, the influence of the natural, cultural, and social environment on the organization and forms of spending free time by children and young people. The text describes factors facilitating and hindering the organization of leisure time of children and young people living in urban areas, as well as selected results of research and reports on leisure time of children and young people spending time in the city. The theoretical considerations examined in the article and the research results cited enabled conclusions for pedagogical practice concerning the free time of children and adolescents in urban areas.